2020
DOI: 10.1038/s41598-019-57185-1
|View full text |Cite|
|
Sign up to set email alerts
|

Moderate Nrf2 Activation by Genetic Disruption of Keap1 Has Sex-Specific Effects on Bone Mass in Mice

Abstract: Keap1 is a negative controller of the transcription factor Nrf2 for its activity. The Keap1/Nrf2 signaling pathway has been considered as a master regulator of cytoprotective genes, and exists in many cell types including osteoblasts and osteoclasts. Our previous study shows Nrf2 deletion decreases bone formation. Recent studies show hyperactivation of Nrf2 causes osteopenia in Keap1 −/− mice, and Keap1 −/− osteoblasts have significantly less proliferative potential than Keap1 +/− osteoblasts. We aimed to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…Our results also provide additional information about sexual dimorphism, observed previously after global Nfe2l2 deletion [ [17] , [18] , [19] , [20] , 22 ]. Although in our study deletion was performed only in the osteoblast/osteocyte lineages, dimorphic effects in bone parameters correlate with differential changes in osteoclast numbers.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Our results also provide additional information about sexual dimorphism, observed previously after global Nfe2l2 deletion [ [17] , [18] , [19] , [20] , 22 ]. Although in our study deletion was performed only in the osteoblast/osteocyte lineages, dimorphic effects in bone parameters correlate with differential changes in osteoclast numbers.…”
Section: Discussionsupporting
confidence: 77%
“…To address the unresolved issues of the role of NRF2 in specific bone cells in vivo , we found evidence that NRF2 activity has an indispensable role in the maintenance of bone homeostasis, both in the cortical and trabecular compartments. Previous studies with global deletion of NRF2 have shown sexual dimorphism in the skeletal phenotype [ [17] , [18] , [19] , [20] , 22 ]. Our data confirm this sexual dimorphism, with more profound effects of NRF2 deletion on bone mass in male mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inhibitory role of DMF, another NRF2 activator in osteoclastogenesis has been shown in both RANKL- and LPS- induced osteolysis models [ 61 ]. Additionally, various KEAP1 deficiency models in which the levels of NRF2 are elevated report increased osteoclastogenesis both in vitro and in vivo [ 65 , 66 ]. Therefore, identifying the downstream effector of NRF2 is important and activating NRF2 in osteoclast precursor cells could be a therapeutic strategy to modulate pathological bone erosion.…”
Section: Discussionmentioning
confidence: 99%